Another Brick in the Wall. Immigration and Electoral Preferences: Direct Evidence from State Ballots - Olivier Bargain; Victor Stephane; Jérôme Valette (Institute of Labor Economics (IZA), 2021)
Using information on actual ballots rather than survey data, we investigate the impact of immigration on both electoral outcomes and immigrant-related motives underlying political preferences. We take advantage of 94 votes, namely 54 policy propositions and 40 elections for candidates, that took place in Californian general elections between 2010 and 2018. We first analyze how the share of immigrants at the census tract level affects electoral outcomes. We find that a rise in immigration is associated with a decrease in people's support for the Democratic party and for liberal measures. Using proposition topics, we show that this effect is driven by policies pertaining to redistribution, public good provision and justice/crime, while other propositions, less directly related to immigration are not impacted. The effect is stronger when immigrants are less assimilated and originate from poor and culturally distant countries.
Keywords: F22; D31; 330; immigration; electoral outcomes